2018
DOI: 10.1002/jmri.26294
|View full text |Cite
|
Sign up to set email alerts
|

Update on multiparametric MRI of urinary bladder cancer

Abstract: 3 Technical Efficacy: Stage 2 J. Magn. Reson. Imaging 2018;48:882-896.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 103 publications
(229 reference statements)
0
34
0
Order By: Relevance
“…Our study revealed mp-MRI diagnostic accuracy of 98.1% in differentiating organ-confined from non-organconfined tumors. This was better than van der Pol et al [1] who reported diagnostic accuracy of 81 to 83% and Afifi et al [15] who reported diagnostic accuracy of 88%.…”
Section: A B C D E Fmentioning
confidence: 54%
See 4 more Smart Citations
“…Our study revealed mp-MRI diagnostic accuracy of 98.1% in differentiating organ-confined from non-organconfined tumors. This was better than van der Pol et al [1] who reported diagnostic accuracy of 81 to 83% and Afifi et al [15] who reported diagnostic accuracy of 88%.…”
Section: A B C D E Fmentioning
confidence: 54%
“…Preoperative staging of urinary bladder carcinomas using TNM system is crucial in the management of bladder cancer which is determined mainly by stage and grade of tumor at diagnosis [1,12].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations